2009
DOI: 10.1111/j.1742-4658.2009.07148.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of synthetic linear tetrapyrroles to probe the verdin sites of human biliverdin‐IXα reductase and human biliverdin‐IXβ reductase

Abstract: Many vertebrate species express two enzymes that are capable of catalysing the reduction of various isomers of biliverdin. Biliverdin‐IXα reductase (BVR‐A) is most active with its physiological substrate biliverdin‐IXα, but can also reduce the three other biliverdin isomers IXβ, IXδ and IXγ. Biliverdin‐IXβ reductase (BVR‐B) catalyses the reduction of only the IXβ, IXδ and IXγ isomers of biliverdin. Therefore, the activity of BVR‐A can be measured using biliverdin‐IXα as a specific substrate. We now show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…BVR-A, the main isoform of BVR (26,36), catalyzes the reduction of BV into BR and is coexpressed with HO-1 in cells of the rat brain that express these enzymes under normal conditions (23). Furthermore, BVR-A is also a serine/threonine/tyrosine kinase that interacts with members of the mitogen-activated protein kinase family, in particular, the extracellular signalregulated kinases 1/2, and once translocated into the nucleus regulates the expression of oxidative stress-responsive genes…”
Section: Resultsmentioning
confidence: 99%
“…BVR-A, the main isoform of BVR (26,36), catalyzes the reduction of BV into BR and is coexpressed with HO-1 in cells of the rat brain that express these enzymes under normal conditions (23). Furthermore, BVR-A is also a serine/threonine/tyrosine kinase that interacts with members of the mitogen-activated protein kinase family, in particular, the extracellular signalregulated kinases 1/2, and once translocated into the nucleus regulates the expression of oxidative stress-responsive genes…”
Section: Resultsmentioning
confidence: 99%
“…Humans have two biliverdin isozymes biliverdin reductase A (BLVRA) and biliverdin reductase B (BLVRB). Although both isozymes are related in conversion, BLVRA converts into bilirubin, a more potent antioxidant (Beale and Cornejo, 1984;Franklin et al, 2009). Recent studies have further suggested a role in ROS Extracts from the cells prepared and analyzed for MAP kinase protein activation by Western blot analysis and band intensity by densitometer.…”
Section: Discussionmentioning
confidence: 98%
“…28 BLVRB was readily detectable in healthy control gel-filtered human platelets with no evidence for altered expression in either BLVRB S111L ET or RT platelets ( Figure 4A ), 30 and uniquely positioned for recognition and/or proton transfer between flavin isoalloxazine and nicotinamide rings. 15 Bacterially expressed and purified recombinant BLVRB WT (wild type) and BLVRB S111L demonstrated disparate NAD(P)H-dependent redox coupling using both flavin-and BV-specific substrates ( Figure 4C-E), the latter uniquely generated by coupled heme oxidation as verdinrestricted BLVRB activity probes retaining no BLVRA cross-reactivity. 15 BLVRB S111L enzymatic activity was defective using flavin mononucleotide (flavin reductase activity; P , .0001) and BV IXb dimethyl esters (BV reductase [BVR] activity; P , .0001), establishing that the S 111 L substitution represents a loss-of-function redox mutation with either substrate.…”
Section: Distinct Patterns Of Blvrb Expression During Erythroid/mk Spmentioning
confidence: 99%
“…15 Bacterially expressed and purified recombinant BLVRB WT (wild type) and BLVRB S111L demonstrated disparate NAD(P)H-dependent redox coupling using both flavin-and BV-specific substrates ( Figure 4C-E), the latter uniquely generated by coupled heme oxidation as verdinrestricted BLVRB activity probes retaining no BLVRA cross-reactivity. 15 BLVRB S111L enzymatic activity was defective using flavin mononucleotide (flavin reductase activity; P , .0001) and BV IXb dimethyl esters (BV reductase [BVR] activity; P , .0001), establishing that the S 111 L substitution represents a loss-of-function redox mutation with either substrate. These results were confirmed in HEK293 cells using lentivirus(Lv)-induced expression, where enhanced BVR activity was evident in HEK293/BLVRB WT -infected cells with little to no activity in HEK293/BLVRB S111L cells compared with HEK293/ Control cells ( Figure 4F); residual BVR activity in HEK293/Control and HEK293/BLVRB S111L reflected endogenous BLVRB expression with no evidence for BLVRA cross-reactivity ( Figure 4G).…”
Section: Distinct Patterns Of Blvrb Expression During Erythroid/mk Spmentioning
confidence: 99%
See 1 more Smart Citation